Pengaruh Kepemilikan Manajerial, Arus Kas Operasi, dan Kompleksitas Operasi Perusahaan Terhadap Ketepatan Waktu Penyampaian Laporan Keuangan - Agis Pratiwi; Tri Utami Lestari (Universitas Sains dan Teknologi Komputer, 2023)
This study aims to examine the influence of the managerial ownership, operating cash flow, and the complexity of the company’s operations on the disclosure of financial information on the official website of the local government. The population in this study are property & real estate sector companies listed on the Indonesia Stock Exchange (IDX) in 2019- 2021. The sampling technique in this study used purposive sampling and obtained 60 samples of companies with a research period of 3 (three) years in order to obtain a total of 180 research observations. The data analysis model used by this study is logical regression analysis using SPSS Version 26 software. The results showed that the managerial ownership, operating cash flow, and the complexity of the company’s operations simultaneously had a significant impact on the timeliness of financial statement reporting. Meanwhile, partially the managerial ownership, operating cash flow, and the complexity of the company’s operations has no a significant effect on the official website on the timeliness of financial statement reporting